Gender, shame and sexual violence: the voices of witnesses and court members at war crimes tribunals - Sharratt, Sara (Ashgate)
Drawing on extensive interview material gathered amongst victims, witnesses, judges and NGOs, this book investigates the prosecution of rape and sexual violence in war crimes tribunals, with special attention to The International Court for the Former Yugoslavia (ICTY) and World Court in Sarajevo. It examines the testimonies of victims and witnesses and their reasons for testifying, their attitudes towards perpetrators, the consequences of testifying, their recommendations for other witnesses and conceptions of justice. In addition, it explores the attitudes of judges, prosecutors, psychologists and those in charge of protecting and offering services. Adopting a feminist approach, "Gender, Shame and Sexual Violence" challenges the assumption that the deterrent effect of making rape trials more visible would reduce the occurrence of sexual violence in conflict situations, contending instead that the manner in which cases are handled both increases the victims` sense of shame and serves to propagate a representation of women`s bodies that may actually serve to increase the use of sexual violence during war. A compelling analysis of the prosecution of rape as a war crime, this volume offers extensive new empirical material that will be of interest to scholars of sociology, gender studies, criminology, politics, international relations and law.